2012
DOI: 10.3354/meps09932
|View full text |Cite
|
Sign up to set email alerts
|

Prey selectivity by juvenile Atlantic cod Gadus morhua in three coastal habitat types

Abstract: Coastal habitats are heavily subjected to eutrophication and commercial fisheries, and such alterations can affect organism interaction strengths and potentially influence trophic dynamics. A key species inhabiting coastal environments in temperate waters is the Atlantic cod Gadus morhua, which utilises coastal areas for food and shelter. We used an experimental mechanistic approach to assay prey selectivity by juvenile cod when foraging on grass shrimp Palaemon elegans and brown shrimp Crangon crangon, under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…habitat (500 strands/m 2 ), and the remaining half of plain open sand habitat. Previous work has shown that prawns are more exposed to predation in less structured habitats [35]. All sides of the tank were opaque except one, to create a clear transparent plexiglas window to observe prawn habitat use.…”
Section: Methodsmentioning
confidence: 99%
“…habitat (500 strands/m 2 ), and the remaining half of plain open sand habitat. Previous work has shown that prawns are more exposed to predation in less structured habitats [35]. All sides of the tank were opaque except one, to create a clear transparent plexiglas window to observe prawn habitat use.…”
Section: Methodsmentioning
confidence: 99%
“…Whether the shrimp reduces its susceptibility to predators by adjusting its activity to habitat structure and visibility to predators is unknown. Vegetation shelters shrimps against predators and a careful adjustment of activity to habitat structure could improve invasion success (Ljungberg et al 2013;Ljungberg et al 2012;Persson et al 2012).…”
Section: Introductionmentioning
confidence: 99%